Hepatic overexpression of protein targeting to glycogen attenuates obesity and improves hyperglycemia in db/db mice - López-Soldado, Iliana; Guinovart, Joan J.; Duran, Jordi (Frontiers in Endocrinology, 2022)
Increased liver glycogen content has been shown to reduce food intake, attenuate obesity, and improve glucose tolerance in a mouse model of high-fat diet (HFD)-induced obesity. Here we studied the contribution of liver glycogen to the regulation of obesity and glucose metabolism in a model of type 2 diabetes and obesity, namely the db/db mouse. To this end, we crossed db/db mice with animals overexpressing protein targeting to glycogen (PTG) in the liver to generate db/db mice with increased liver glycogen content (db/db-PTG). Hepatic PTG overexpression reduced food intake and fat weight and attenuated obesity and hyperglycemia in db/db mice. Db/db-PTG mice showed similar energy expenditure and physical activity to db/db mice. PTG overexpression reduced liver phosphoenolpyruvate carboxykinase (PEPCK) protein levels and repressed hepatic glucose production in db/db mice. Moreover, increased liver glycogen elevated hepatic ATP content in these animals. However, lipid metabolism was not modified by PTG overexpression. In conclusion, increased liver glycogen content ameliorates the diabetic and obesity phenotype in db/db mice.